PROJECT BASED LEARNING THROUGH "SEVIMA EDLINK APPS TO IMPROVE STUDENTS' ACADEMIC WRITING OF EDUCATION PROGRAM AT STKIP KUSUMANEGARA - Dini Fitriani; Awin Alaby; Wisnu Kala Kusumajati (Journal of English Language Teaching and Literature (JELTL), 2022)
Distance Learning is a big challenge for the world of education because not all have experienced it before. Project Based Learning (PBL) through Edlink Sevima Application is one alternative that can be applied by lecturers in Distance Learning activities. The purpose of this study was to determine whether the Project Based Learning (PBL) as Learning Model through the Edlink Sevima Application could improve the academic writing skills of students of the English Education Study Program at STKIP Kusumanegara. This research was conducted with a Classroom Action Research (CAR) research approach which consisted of two learning cycles with 18 students. The data collection technique used is through observation, interviews, and student academic writing tests. The results of this study can be seen by using the Project Based Learning learning model through edlink sevima which can improve students' academic writing test results from two learning cycles given a minimum completeness score of 75 and a success target of 85%. In the first cycle students were able to achieve the target of 6i%, and the second cycle 90%. Based on the results of the study, it can be said that the Project Based Learning as a learning model through the Sevima edlink application is effective in improving students' academic writing skills in distance learning. Key words: Project Based Learning, Edlink Sevima, Academic Writing.